A Study of Learning Achievement Problem-Solving Fraction, Decimal Unit and Mathematical Skills and Process of Grade 6 Students by K-W-D-L Technique - งานจัตุรัส, ปิยะนันท์; จงกลกลาง, สิรินาถ (Ratchaphruek Journal, 2019)
The purpose of the study were to 1) compared learning achievement on problem-solving fraction, decimal unit from grade 6 students before and after by K-W-D-L technique 2) compared learning achievement on problem-solving fraction, decimal unit and mathematical skills and process of grade 6 students after by K-W-D-L technique with the criteria score of 70%. 3) compared mathematical skills and process from grade 6 students after by K-W-D-L technique with the criteria score of 70%. The simples were 15 students form grade 6 in the first semester of academic year 2018 at Ban Kaen Thao School Sung Noen District, Nakhon Ratchasima. Nakhon Ratchasima Primary Education Service Area Office 4. The research instrument were lesson plans problem-solving fraction, decimal unit. The experimental instrument were leaning achievement test and mathematical skills and process evaluation form. The data was using mean (), standard deviation (S.D.), percentage and t-test. The finding of study were as folloes : Learning achievement from grade 6 students with problem-solving fraction, decimal unit revealed that after learning score was higher than before leaning score significantly at the .05 level. Learning achievement from grade 6 students with problem-solving fraction, decimal unit revealed that after learning was higher than the criterion score of 70% and after learning score was significantly at the .05 Learning achievement from grade 6 students with problem-solving fraction, decimal unit revealed that after learning was higher than the criterion score of 70% mathematical skills and process was lower than the criterion score of 70% and after learning score was significantly at the .05 level significantly. Keywords: K-W-D-L technique, mathematical skills and process, mathematical skills